Marine Ecolexicon of the Klampis Barat Community, Klampis Subdistrict, Bangkalan Regency - Mutmainnah; Khusnul Khotimah; Arief Setyawan (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study aims to describe the form and meaning of marine ecolexicons used by the people of West Klampis, Klampis District, Bangkalan Regency, and to explain how these lexicons represent the ecological and cultural knowledge of the Madurese coastal community. This study uses a qualitative descriptive method with an ecolinguistic approach. Data were obtained through participant observation, in-depth interviews with fishermen and fish traders, and documentation. Data analysis was conducted using Miles and Huberman's interactive model, which includes data reduction, data presentation, and conclusion drawing and verification. The results of the study show that there are 40 marine ecolexicons grouped into four main categories, namely marine products lexicon, fishing tools, marine weather, and fishing activities. In addition, grammatically, these marine ecolexicons consist of two main forms, namely nouns and verbs. Each category illustrates the close relationship between language, environment, and cultural practices of coastal communities. The marine product lexicon reflects the community's knowledge of marine biodiversity and its economic value. The fishing tools lexicon shows the community's adaptive ability in creating and utilizing fishing gear according to environmental conditions. The marine weather lexicon shows the community's sensitivity to natural signs. Meanwhile, the fishing activities lexicon describes work patterns, strategies, and ecological experiences that have been passed down from generation to generation. These findings confirm that the marine ecolexicon of the West Klampis community not only functions as a means of communication but also as a representation of the ecological knowledge and cultural identity of the coastal Madurese community.